Genetic containment in vegetatively propagated forest trees: CRISPR disruption of LEAFY function in Eucalyptus gives sterile indeterminate inflorescences and normal juvenile development. Issue 9 (4th May 2021) - Elorriaga, Estefania; Klocko, Amy L.; Ma, Cathleen; du Plessis, Marc; An, Xinmin; Myburg, Alexander A.; Strauss, Steven H.
Summary: Eucalyptus is among the most widely planted taxa of forest trees worldwide. However, its spread as an exotic or genetically engineered form can create ecological and social problems. To mitigate gene flow via pollen and seeds, we mutated the Eucalyptus orthologue of LEAFY (LFY) by transforming a Eucalyptus grandis × urophylla wild‐type hybrid and two Flowering Locus T (FT) overexpressing (and flowering) lines with CRISPR Cas9 targeting its LFY orthologue, ELFY . We achieved high rates of elfy biallelic knockouts, often approaching 100% of transgene insertion events. Frameshift mutations and deletions removing conserved amino acids caused strong floral alterations, including indeterminacy in floral development and an absence of male and female gametes. These mutants were otherwise visibly normal and did not differ statistically from transgenic controls in juvenile vegetative growth rate or leaf morphology in greenhouse trials. Genes upstream or near to ELFY in the floral development pathway were overexpressed, whereas floral organ identity genes downstream of ELFY were severely depressed. We conclude that disruption of ELFY function appears to be a useful tool for sexual containment, without causing statistically significant or large adverse effects on juvenile vegetative growth or leaf morphology.